Ultrafast photonics applications of zirconium carbide as a novel mode-locker for fiber lasers. Issue 47 (18th November 2021) - Liu, Sicong; Lv, Ruidong; Wang, Jiang; Wang, Yishan; Wang, Hushan; Zhang, Han; Wang, Yonggang
Abstract : This work pioneers the application of a ZrC-based device as a mode-locker to achieve ultrashort pulses. Abstract : Zirconium carbide (ZrC), as a novel member of the MXene family, has outstanding physical and chemical properties; however, the applications of ZrC in ultrafast photonics are still rare. Herein, a ZrC film was deposited by magnetron sputtering deposition (MSD) technology onto a D-shaped fiber and the nonlinear optical properties of the ZrC film were demonstrated. MSD technology is an advanced preparation method applicable to various materials. The saturation intensity and the modulation depth of the ZrC film were measured to be 197.6 MW cm −2 and 11.9%, respectively. After inserting the ZrC SA into an erbium-doped fiber laser (EDFL) cavity, a passive mode-locked EDFL pulse was formed. In mode-locked operation, conventional solitons with an ultrashort pulse duration of 395 fs and an output power of 49.86 mW were achieved in the communication band. The corresponding central wavelength of the output spectrum was 1562.19 nm with a 7.73 nm spectral width. This work pioneers the application of a ZrC-based device as a mode-locker to achieve ultrashort pulses for the first time and expands the application of the ZrC material. The experimental results open new opportunities for the use of ZrC in mode-locked lasers and photonics applications.